j = 0 ∑ 1 3 i = 0 ∑ j ( i 1 3 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S = j = 0 ∑ 1 3 i = 0 ∑ j ( i 1 3 ) = j = 0 ∑ 1 3 ( j 1 3 ) ( 1 4 − j ) = 1 4 j = 0 ∑ 1 3 ( j 1 3 ) − j = 0 ∑ 1 3 ( j 1 3 ) j = 1 4 ⋅ 2 1 3 − j = 0 ∑ 1 3 j ! ( 1 3 − j ) ! 1 3 ! ⋅ j = 1 4 ⋅ 2 1 3 − j = 0 ∑ 1 2 j ! ( 1 2 − j ) ! 1 3 ⋅ 1 2 ! = 1 4 ⋅ 2 1 3 − 1 3 j = 0 ∑ 1 2 ( j 1 2 ) = 1 4 ⋅ 2 1 3 − 1 3 ⋅ 2 1 2 = 6 1 4 4 0
Can you please explaining the second line of your answer how you do it
Log in to reply
I have added a line to explain. Hope that it is useful.
Problem Loading...
Note Loading...
Set Loading...
I have a method which uses only the identity that k = 0 ∑ n ( k n ) = 2 n . We can rewrite the summation in the following array:
( 0 1 3 ) + ( 0 1 3 ) + ( 0 1 3 ) + ⋮ ( 1 1 3 ) + ( 1 1 3 ) + ( 2 1 3 ) + ⋱
Let the first row be Row 1, the second row be Row 2, etc. Notice that the sum of Row n and Row 1 4 − n have the same sum. For example, Row 1 is ( 0 1 3 ) and Row 13 is ( 0 1 3 ) + ( 1 1 3 ) + … + ( 1 2 1 3 ) , converting ( 0 1 3 ) to ( 1 3 1 3 ) for Row 1, we get that the sum will have the exact terms as Row 14. We can do this similarly for Rows 2, 3, 4, 5 and 6. If we add Row 7 to itself, we can also do this, so the sum of Row 7 is half that of Row 14. The sum of Row 14 is 2 1 3 , so the total sum (remembering to add Row 14 as well) is 2 1 5 × 2 1 3 = 6 1 4 4 0 .
We can generalise this sum to ( n + 2 ) 2 n − 1 , where n = 1 3 in this case.